HUBUNGAN ANTARA KELELAHAN KERJA DENGAN STRES KERJA PADA TENAGA KERJA DI LABORATORIUM PCR RSU BUNDA THAMRIN TAHUN 2023 - Linggom, Tampak; Prima, Armanda; Anggita, Rizliana (Deli Medical and Health Science Journal, 2023)
This research was conducted on workers at the PCR Laboratory of Bunda Thamrin in 2020-2021 to determine the relationship between work fatigue and work stress in workers. Work fatigue is a process of decreasing efficiency, work performance, and reduced endurance or physical strength of the body to continue the activities that must be done. Work stress is a pressure that cannot be tolerated by individuals both from within themselves and from outside themselves. This type of research was an analytic observational study with cross sectional approach. The time of the study was carried out in December 2020-July 2021. The population in this study were all workers who worked at PCR Laboratory of Bunda Thamrin, totaling 30 workers. Sampling was done by total sampling technique. Data collection methods were obtained from primary data and secondary data. The results of this study were processed by using Fisher's exact test. From the results of chi-square test, the relationship between work fatigue and work stress in the workforce at PCR Laboratory of Bunda Thamrin, it can be seen that 18 respondents who stated that they were tired, 13 of them had a level of work stress, stress (72,2%), while of the 12 respondents who said they were tired, 13 of them had work stress levels. stated that they are not tired 9 of them have work stress levels, not stress (75,0 %). With the P-value obtained from the output table, namely the Exact Fisher Test (P = 0,024), which is smaller than = 0,05. Based on these results, it can be concluded that there is a relationship between work fatigue and work stress on the workforce in the PCR Laboratory Bunda Thamrin. There is a relationship between work fatigue and work stress at PCR Laboratory of Bunda Thamrin in 2023 with a P-value = 0,024 < = 0,05. It is expected that workers do not force themselves to do their work and stretch their muscles or take a short break if they feel tired.